Thermo-Mechanical Stability Analysis of Hollow Cellular Concrete Block Air Convection Embankments for Cold Regions - Wu, H.; Zhang, X.; Liu, J. (IOP Conference Series: Earth and Environmental Science, 2024)
Crushed-rock air convection embankment (ACE), as a highly open-graded porous medium, has been used to mitigate the thaw settlement of pavement structures in permafrost regions. Previous studies have revealed that cellular concrete has significant potential as a cost-effective material for ACE to solve the problem of crushed rock shortage in interior Alaska and improved the thermal stability of pavement structures in cold climates. the design configurations of the hollow cellular concrete block ACE were further designed to maximize the performance benefits and facilitate future implementation and field construction. However, the mechanical behaviors of the proposed structures and ice-rich subgrade were still unknown. in this study, a thermo-mechanical coupling model was developed to evaluate the thermal effect on the long-term mechanical stability of the selected pavement structures and subgrade soils. the results indicated that the thermal stability of the proposed hollow cellular concrete block ACEs was superior to that of the conventional crushed-rock ACE. the maximum thaw settlement of the proposed hollow cellular concrete block ACE was only 13.4% that of the conventional crushed-rock ACE. Thermal and mechanical analyses showed that the proposed cellular concrete ACEs have a significant advantage over conventional crushed-rock ACE.